2020
DOI: 10.1007/s10495-020-01627-z
|View full text |Cite
|
Sign up to set email alerts
|

BAX-dependent mitochondrial pathway mediates the crosstalk between ferroptosis and apoptosis

Abstract: Ferroptosis is considered a distinctive form of cell death compared to other types of death such as apoptosis. It is known to result from iron-dependent accumulation of lipid peroxides rather than caspase activation. However, we reported recently that ferroptosis interplays with apoptosis. In this study, we investigated a possible mechanism of this interplay between ferroptosis and apoptosis. Results from our studies reveal that combined treatment of the ferroptotic agent erastin and the apoptotic agent TRAIL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 20 publications
1
42
0
Order By: Relevance
“…Consistently, Lee et al. described that although combination therapy with TRAIL and other compounds could make human colon cancer HCT116 cell line susceptible to TRAIL, Bax-deficient cells but not Bak-deficient cells, restored their resistance to TRAIL ( 50 ). In sum, these findings imply that the TRAIL-induced apoptosis is closely linked to Bax-mediated mitochondria-dependent pathway.…”
Section: Mechanisms Of Cancer Resistances To Trailmentioning
confidence: 85%
“…Consistently, Lee et al. described that although combination therapy with TRAIL and other compounds could make human colon cancer HCT116 cell line susceptible to TRAIL, Bax-deficient cells but not Bak-deficient cells, restored their resistance to TRAIL ( 50 ). In sum, these findings imply that the TRAIL-induced apoptosis is closely linked to Bax-mediated mitochondria-dependent pathway.…”
Section: Mechanisms Of Cancer Resistances To Trailmentioning
confidence: 85%
“…In addition, Bax and Bcl-2 are potentially central regulators of apoptosis, necroptosis, and ferroptosis as they serve as crosstalk between these cell death pathways [ 45 48 ]. Our data showed that Bax/Bcl-2 was remarkably decreased by all cell death inhibitors and might involve in neuroprotection following cardiac I/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…In our recent article [1], we report that ER stress response plays a pivotal role in the crosstalk between ferroptosis and apoptosis. Dr. Yoshida constructively criticizes that TRAIL treatment alone leads to JC-1 aggregation and combined treatment of TRAIL and erastin results in mitochondrial depolarization which is indicated by an increase in JC-1 fluorescence intensity.…”
Section: Replymentioning
confidence: 99%